(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2025)
In the process of the emancipation of film music that took place in the first decades after World War II, the filmography of Michelangelo Antonioni and Andrei Tarkovsky offers multiple points of interest. Tarkovsky’s well-established relationship with Eduard Artemiev, matured within the Moscow studio, allowed Tarkovsky to use electronic sounds in some of his films, such as Solaris, in a manner far removed from the worn-out standards of science-fiction cinema. Likewise, Antonioni found in the music of Vittorio Gielmetti a suitable aural commentary on the mental disorders of the protagonist in Deserto rosso, inserting electronic music into the palette to describe the horizons of the inner human psyche. In both cases, the presence of noise is effectively combined with music to create a very complex sound texture.